1970
DOI: 10.4141/cjps70-119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fertilizer-Nitrogen and Water Supply on Distribution of Dry Matter and Nitrogen Between the Different Parts of Wheat

Abstract: Wheat in pots and in the field was subjected plied at the boot stage of growth, N increased to different watering regimes and fertilizer-N, dry matter much less than when applied at either as ammonium-N with a nitrification sowing, but increased the percent N in the inhibitor or as nitrate-N, was applied at sow-grain. Divided dressings, half at sowing and ing or during growth. More weight of leaves half during growth, increased yield and N and stems was produoed during early growth uptake by the same amount as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
16
1

Year Published

1973
1973
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 11 publications
6
16
1
Order By: Relevance
“…Under the more optimum moisture conditions, N had no effect on straw-grain ratio. Similar to the findings of Spratt and Gasser (1970) (Table 2).…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…Under the more optimum moisture conditions, N had no effect on straw-grain ratio. Similar to the findings of Spratt and Gasser (1970) (Table 2).…”
Section: Methodssupporting
confidence: 81%
“…They suggested that the N in the grain was derived primarily by translocation from leaves, stems and chaff rather than from further absorption from the soil. Spratt and Gasser (1970) found that drought caused the extra N derived from the fertilizer to remain in the straw at harvest. Sosulski et al (1966 have suggested that N fertility is the principal factor <:ontrolling the protein in grain, while soil mr:isture was more important in controllingJ yields; but Hutcheon and Rennie (1960) …”
mentioning
confidence: 99%
“…White and Brown (1972) also showed that doubling the N fertilization rate decreased the percentage of N recovered in Stipa viridula Trin. Similar results were reported by Spratt and Gasser (1970) and Simonis (1988). Bittman and Kowalenko (1998), however, reported a greater % of N recovery of applied as N fertilization rates Table 6.…”
Section: Nitrogen Recoverysupporting
confidence: 81%
“…On the other hand, the N uptake by the crops during the period described above was also increased by irrigation in that period. Since many authors (Tanaka and Gracia 1965;Spratt and Gasser 1970;Novoa and Loomis 1981;Simmons 1987) indicated that tiller production increasedwith the increase in the N uptake by cereal crops, it can be considered that the increase in the number of tillers during the beginning of tillering to the milky stage was caused by the promotive effect of irrigation on N absorption by the crops.…”
Section: Discussionmentioning
confidence: 99%
“…This situation does not allow for precise field investigations, especially in attempts to determine whether there are critical stages in crop development, at which even a small amount of irrigation water exerts a significant effect on the yield. Many researchers, therefore, have attempted to prevent field experiments from being affected by rain by using shelters to determine the optimum irrigation time or growth stage (Spratt and Gasser 1970;Wells and Dubetz 1970;Day et al 1978), though the crop micro-climate may be influenced by prolonged covering .…”
mentioning
confidence: 99%